Sustainable development of natural fiber composite material. (2021) - Balachandar, M.; Vetre Selvan, E.; Ponshanmugakumar, A.; Magesh, S.; Ramanan, N.
Abstract: The braking system is most important system in automotive. In earlier days asbestos is used as braking materials which causes so many environmental problems. To overcome such situations, natural fibres can be used. Natural fibers will be a promising replacement of asbestos. Asbestos have long been known to cause lung and other cancerous diseases. The use of asbestos is being avoided because of its health implications such as carcinogenic and harmful nature. Universal Testing Machine (UTM) clamping device materials and materials used for brake pads in automobiles should have stable and reliable frictional and wear properties so that they can withstand varying conditions of load, velocity, temperature and high durability. Many new natural composites are developed for the application of braking system in automotives. Vetiver fiber inner coated with glass fiber are selected for the suitable replacement of existing brake pad. It is subjected to Dynamic Mechanical Analysis, wear testing, tensile testing, compression testing and flexural testing etc